Penguatan Komunikasi Inklusif melalui Workshop Bisindo bagi Mahasiswa Pendidikan Dasar - Satriana, Eny; Khaltsum, Ummu; Amadyah, Nurul; Defianty, Sartika (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
Inclusive education requires prospective teachers to be prepared to establish equal communication with all students, including Deaf and hard-of-hearing learners. However, in practice, Elementary Education students still face limitations in mastering Indonesian Sign Language (Bisindo), hindering effective inclusive communication. This situation underscores the importance of a community service program focused on strengthening inclusive communication competencies for prospective elementary school teachers. This community service activity aims to improve Elementary Education students’ readiness for inclusive teaching through an Indonesian Sign Language (Bisindo) workshop. The method employed is a participatory community service approach involving Elementary Education students as participants, the Deaf community, and sign language interpreters as activity partners. The program included delivery of basic Bisindo material, direct communication practice, and reflective learning experiences. Data were collected through observation during the activities, reflective interviews with participants, and documentation, then analyzed descriptively and qualitatively. The results indicate an increase in students’ understanding of inclusive communication concepts, basic Bisindo skills, and the development of empathy and openness toward student diversity. Overall, this activity contributes significantly to preparing prospective teachers who are more responsive and ready to implement inclusive teaching in elementary schools.